Bibliometric analysis of postoperative deep vein thrombosis in total hip arthroplasty using CiteSpace - Ren, Xi; Han, Changxu; Nie, Jiaxu; Bai, Junwei; Zhang, Litian (Frontiers in Surgery, 2025)
BackgroundThere was a lack of bibliometric analyses of postoperative deep vein thrombosis (DVT) after total hip arthroplasty (THA), and this study aimed to provide a comprehensive overview of the knowledge structure and research hotspots in this area through visual analyses.MethodThe Web of science (WOS) core databases were searched for relevant studies built up to March 2024, and CiteSpace was then used to create a network diagram, analyze the authors, institutions, nations, journals, keywords, and references in this field generally, as well as to investigate hotspots and trends in research in this field.ResultsThere were 1,299 pertinent papers in all, and the number of publications in the topic was generally rising. The author with the highest number of publications is Parvizi, Javad, and the institution is Jefferson University, while the United States is the most influential and contributing country in the field, the top 5 high frequency keywords are venous thromboembolism, deep vein thrombosis, prevention, total hip arthroplasty, replacement; the keyword dabigatran etexilate has the highest burst intensity in burst detection, while aspirin, blood management, and risk stratification are emerging research trends.ConclusionThis study examines the literature on postoperative DVT following THA using CiteSpace, which offers useful data for possible cooperation between authors, countries, and research institutions. It also identifies hotspots and trends for future research, which will be a resource for scholars looking to delve deeper into the preventive measures for DVT following THA.